2020
DOI: 10.1101/2020.08.15.241349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of SARS-CoV-2 Mutations on Protein Structures and Intraviral Protein-Protein Interactions

Abstract: Since 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) has infected ten millions of people across the globe, and massive mutations in virus genome have occurred during the rapid spread of this novel coronavirus. Variance in protein sequence might lead to change in protein structure and interaction, then further affect the viral physiological characteristics, which could bring tremendous influence on the pandemic. In this study, we investigated 18 no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Though functionally tolerated this change was predicted to decrease the protein stability. This finding is similar with other studies that reported R203K and G204K destabilizes N protein structure but may enhance interaction with SARS-CoV-2 Envelop protein that may promote viral release (53,54).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Though functionally tolerated this change was predicted to decrease the protein stability. This finding is similar with other studies that reported R203K and G204K destabilizes N protein structure but may enhance interaction with SARS-CoV-2 Envelop protein that may promote viral release (53,54).…”
Section: Discussionsupporting
confidence: 92%
“…There two other functionally significant mutations which are Q57H in ORF3a and S194L in N protein. Our analysis suggested the Q57H decreases protein stability with altered protein function may result in loss of a CD4+ T Cell epitope similar to other studies (53,56). The S194L was predicted to have neutral effect in our study with a reduced DDG value and may attenuate viral assembly as reported in an earlier study (53).…”
Section: Discussionsupporting
confidence: 88%
“…Mutation is one of the main mechanisms by which viruses are constantly changing due to genetic selection. Although most point mutations are neutral and do not alter the protein the gene codes for, a few favorable mutations can give an evolutionary advantage to viruses (Wu et al, 2020). The D614G substitution in the gene encoding the spike protein emerged in late January or early February 2020, and emerged in Europe around 2020 February 22 (Korber et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A222V has recently been reported as a rapidly increasing genotype (Bartolini et al, 2020; Ward et al, 2021). Q57H of ORF3a has been reported that it shows an opposing association with decreased deaths and increased cases per million (Oulas et al, 2021), It also causes significant structural changes that affect the interaction between ORF3a and other proteins (Wu et al, 2020). From the level of molecular simulation, our study explored the change of protein traits when D614G and A222V were coupled for S protein, and the influence of Q57H on protein traits for ORF3a protein.…”
Section: Discussionmentioning
confidence: 99%
“…Four such mutations (Q57H and G251V in ORF3a, R203K/G204R in N proteins) have been reported. Q57H increases the affinity of ORF3a for S and N proteins resulting in an impact on virus budding and release [149]. On the contrary, some mutations (like P323L in NSP12 and D614G in S protein) do not affect the protein biology of the virus but play a role in RNA structures [150].…”
Section: Mutations and Haplotype Studiesmentioning
confidence: 99%